2018
DOI: 10.15252/embj.201898984
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone signaling restricts hematopoietic stem cell expansion during puberty

Abstract: The number and self-renewal capacity of hematopoietic stem cells (HSCs) are tightly regulated at different developmental stages. Many pathways have been implicated in regulating HSC development in cell autonomous manners; however, it remains unclear how HSCs sense and integrate developmental cues. In this study, we identified an extrinsic mechanism by which HSC number and functions are regulated during mouse puberty. We found that the HSC number in postnatal bone marrow reached homeostasis at 4 weeks after bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Outside of the ovary, the LHR is expressed in the uterus and oviduct (58), although LHR expression in these tissues is not required for reproduction (59). Outside of the reproductive system, recent evidence indicates that the LHR functions in hematopoietic stem cells (60). Likewise the NPR2 guanylyl cyclase functions in the skeletal, cardiovascular, and nervous systems ( 61), but its localization is not well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of the ovary, the LHR is expressed in the uterus and oviduct (58), although LHR expression in these tissues is not required for reproduction (59). Outside of the reproductive system, recent evidence indicates that the LHR functions in hematopoietic stem cells (60). Likewise the NPR2 guanylyl cyclase functions in the skeletal, cardiovascular, and nervous systems ( 61), but its localization is not well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…We found the luteinizing hormone/choriogonadotropin receptor gene ( Lhcgr ) as part of the hormone regulatory process and that exclusively overlaps with differential A compartments in LT and ST-HSCs ( Supplementary Figure 3D ). A previous study [61] identified the Lhcgr gene as highly critical in regulating the HSC homeostasis and showed that its loss leads to abnormally elevated hematopoiesis and leukocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is extensive evidence linking fat replacement in the marrow of adults to steroid therapy, there are no data linking the increase in marrow fat to the surge of sex steroid hormones at puberty. A recent study in a preclinical mouse model has elegantly demonstrated that leutinizing hormone is involved in hematopoietic stem-cell homeostasis (22); it may well be that the expression of this receptor particularly at sites within long bones and where hematopoietic function is no longer needed after puberty is one molecular mechanism driving the replacement of this functionally active tissue with fat.…”
Section: Discussionmentioning
confidence: 99%